1998
DOI: 10.1523/jneurosci.18-04-01318.1998
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Axotomy Induces Long-Term c-Jun Amino-Terminal Kinase-1 Activation and Activator Protein-1 Binding Activity by c-Jun and junD in Adult Rat Dorsal Root GangliaIn Vivo

Abstract: One of the earliest documented molecular events after sciatic nerve injury in adult rats is the rapid, long-term upregulation of the immediate early gene transcription factor c-Jun mRNA and protein in lumbar dorsal root ganglion (DRG) neurons, suggesting that c-Jun may regulate genes that are important both in the early post-injury period and during later peripheral axonal regeneration. However, neither the mechanism through which c-Jun protein is increased nor the level of its post-injury transcriptional acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
142
0
2

Year Published

2000
2000
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(155 citation statements)
references
References 80 publications
11
142
0
2
Order By: Relevance
“…p75 activates JNK1 and 3 in oligodendrocytes JNK activity has been shown to increase as PC12 cells differentiate (Eilers et al, 1998) and to remain elevated after axotomy of adult dorsal root ganglion neurons (Kenney and Kocsis, 1998). Similarly, cerebellar granule neurons exhibit a high basal level of JNK activity (Coffey et al, 2000).…”
Section: Results P75 Protein Is Required For Ngf-dependent Apoptosis mentioning
confidence: 99%
“…p75 activates JNK1 and 3 in oligodendrocytes JNK activity has been shown to increase as PC12 cells differentiate (Eilers et al, 1998) and to remain elevated after axotomy of adult dorsal root ganglion neurons (Kenney and Kocsis, 1998). Similarly, cerebellar granule neurons exhibit a high basal level of JNK activity (Coffey et al, 2000).…”
Section: Results P75 Protein Is Required For Ngf-dependent Apoptosis mentioning
confidence: 99%
“…Activation of AP-1, which is a homo-or heterodimer of c-fos and c-jun basic leucine zipper transcription factors, is sufficient to induce neurite outgrowth in PC12 cells (34). In addition, AP-1 binding to its promoter region is dramatically increased immediately following sciatic nerve injury and remains active while neurons are regenerating (35). We found that GEFT is capable of upregulating the activities of both NF-B and AP-1 transcription factors via activation of the Rho family of small GTPases.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that activation of the Rho family of small GTPases leads to the MAPK-dependent activation of a number of transcriptional factors involved in cell proliferation and survival in a diverse number of cell types (33). Specifically, the AP-1 transcription factor, consisting of homo-or heterodimers of c-fos and c-jun, has been shown to be sufficient to induce neurite outgrowth in PC12 cells (34) and play a role in the initial regeneration of neurons after severe injury (35). In addition, the NF-B signaling cascade has been found to be important for both neurite outgrowth and neuron survival (36).…”
Section: Fig 7 Geft Induction Of Neurite Outgrowth Is Via Pak1 and mentioning
confidence: 99%
“…Of the signaling pathways associated with neuronal death, a role for the stress-activated protein kinase͞c-Jun N-terminal kinase (SAPK͞JNK) signaling pathway has been implicated in nerve injury (4,5). In this regard, correlative studies have described increased expression of c-Jun and JNK activity after axotomy (6)(7)(8).…”
mentioning
confidence: 99%